Pengaruh Model Kooperatif TPS Berbantuan Procam X Lite Terhadap Keaktifan Dan Hasil Belajar Kognitif Siswa Kelas X Di SMK Kristen (Bisnis & Manajemen) Salatiga - Jelmi Palentina; Adriyanto Juliastomo Gundo (Jurnal Ilmiah Wahana Pendidikan, 2023)
The objective of this research is to assess the effects of the TPS cooperative model, facilitated by ProCam X-Lite, on the students' active participation and cognitive learning at the 10th grade level at SMK Kristen (Bisnis & Manajemen) Salatiga. The pretest-posttest control group design kind of True Experimental Design is used in this study. From a total of four classes, two were randomly selected, with the X Marketing class serving as the experimental group and the X Accounting & Finance class serving as the control group. The instruments utilized in this study include questionnaires, cognitive tests, and student activity observation sheets. Based on the values obtained from the activeness observation sheet, The average posttest score for the experimental class is 80.45, whereas the average for the activeness observation sheet values is 81.81. Meanwhile, The control class's posttest scores on average were 53.84, while the average level of involvement on the observation sheet for that class was 51.70. The findings of the t-test revealed that the students' cognitive learning outcomes produced a p-value of 0.004 and that the level of student involvement produced a p-value of 0.000. From these results, it can be concluded that the use of the cooperative TPS model with the assistance of ProCam X-Lite has a significant impact on the engagement and cognitive learning outcomes of 10th-grade students at SMK Kristen (Bisnis & Manajemen) Salatiga, as indicated by the fact that this p-value is less than 0.05.